An entropy optimization study of non-Darcian magnetohydrodynamic Williamson nanofluid with nonlinear thermal radiation over a stratified sheet. (December 2021) - Bilal, Muhammad; Ramzan, Muhammad; Mehmood, Yasir; Kbiri Alaoui, Mohammed; Chinram, Ronnason
The assessment of the Darcy–Forchheimer flow of magnetohydrodynamic Williamson nanofluid with entropy optimization is the main purpose of this article. This study was carried out to analyze the impacts on fluid flow via a stratified plate. The impacts of viscous dissipation, chemical reaction, and Joule heating are examined in the existence of nonlinear thermal radiation. The framework of partial differential expressions is transformed into ordinary differential equations by utilizing a suitable set of similarity transformations. The obtained differential equations are analytically tackled by the homotopy analysis approach.ℏ -curves, table of convergence, and graphical outcomes are displayed and examined by using MATHEMATICA software. A distinctive parameter chart, against the profiles of temperature, velocity, and concentration with relevant discussion is portrayed for emphasizing their physical importance. Through graphical representations, the Sherwood number, the coefficient of skin friction, local Nussel1t number, and entropy generation impact are examined. This kind of study is useful in many industries like solar engineering, polymer extrusion, electronic supplies, biomedical, etc.